Genomic and proteomic analyses of Nus-dependent non-lambdoid phages reveal a novel coliphage group prevalent in gut: mEpimmI - Honorio Negrete-Méndez; Guadalupe Valencia-Toxqui; Omar A. Sepúlveda-Robles; Emmanuel Ríos-Castro; Jairo C. Hurtado-Cortés; Victor Flores; Adrián Cázares; Luis Kameyama; Eva Martínez-Peñafiel; Fernando Fernández-Ramírez (Frontiers in Microbiology)
IntroductionNus-dependent Mexican Escherichia coli phages (mEp) were previously isolated from clinical samples of human feces. Approximately 50% corresponded to non-lambdoid temperate phages integrating a single immunity group, namely immunity I (mEpimmI), and these were as prevalent as the lambdoid phages identified in such collection.MethodsIn this work, we present the structural and functional characterization of six representative mEpimmI phages (mEp010, mEp013, mEp021, mEp044, mEp515, and mEp554). In addition, we searched for homologous phages and prophages in the GenBank sequence database, and performed extensive phylogenetic analyses on the compiled genomes.ResultsA biological feature-based characterization of these phages was carried out, focusing on proteins relevant to phage biological activities. This included mass spectrometry analysis of mEp021 virion structural proteins, and a series of infection assays to characterize the function of the main repressor protein and the lipoproteins associated with superinfection-exclusion; to identify the main host receptor proteins recognized by these phages and the prophage insertion sites within the host genome, which were associated with specific integrase sequence-types present in the viral genomes. Further, we compiled 42 complete homologous genomes corresponding to 38 prophages from E. coli strains and 4 phages from metagenomes, displaying a wide geographical distribution. Intergenomic distance analyses revealed that these phages differ from previously established phage clades, and whole-proteome similarity analyses yielded a cohesive and monophyletic branch, when compared to >5,600 phages with dsDNA genomes.DiscussionAccording to current taxonomic criteria, our results are consistent with a novel family demarcation, and the studied genomes correspond to 9 genera and 45 distinct species. Further, we identified 50 core genes displaying high synteny among the mEpimmI genomes, and these genes were found arranged in functional clusters. Furthermore, a biological feature-based characterization of these phages was carried out, with experiments focusing on proteins relevant to phage biological activities, revealing common traits as well as diversity within the group. With the integration of all these experimental and bioinformatics findings, our results indicate that the mEpimmI phages constitute a novel branch of Caudoviricetes distinct to other known siphovirus, contributing to the current knowledge on the diversity of phages infecting Escherichia coli.